Bear bile use at the intersection of maternal health in Cambodia - Elizabeth Oneita Davis; Mhairi Gibson; Thona Lim; Jenny Anne Glikman (BMC, 2020)
Abstract Background The consumption of bear gallbladders and bear bile in Southeast Asia is a persistent threat to bear populations. As part of a larger effort to understand the characteristics of bear part consumption in Cambodia, we uncovered a consumer base of women seeking treatment for post-partum and uterine ailments. Methods To better understand this aspect of consumption, we interviewed 122 women in seven different provinces in Cambodia, probing into the motivations and influences for using bear bile, as well as what types of ailments Cambodian women use it for. Results We found that it is generally used by young or expecting mothers, and for such issues as post-partum "fatigue" (toas in Khmer), which could encompass post-partum depression. A desire to be supported by kin networks seems to facilitate the continued use of bear gallbladder and bile for these purposes. Conclusions We suggest that efforts to reduce consumption should focus on encouraging older kin to change their means of support to Western/biomedical and by extension non-wildlife alternatives.